Increase in backbone mobility of the VTS1p-SAM domain on binding to SRE-RNA - Ravindranathan, Sapna; Oberstrass, Florian C.; Allain, Frederic H. T. (Journal of Molecular Biology, 2010)
The sterile alpha motif (SAM) domain of VTS1p, a posttranscriptional gene regulator, belongs to a family of SAM domains conserved from yeast to humans. Even though SAM domains were originally classified as protein-protein interaction domains, recently, it was shown that the yeast VTS1p-SAM and the SAM domain of its Drosophila homolog Smaug can specifically recognize RNA hairpins termed Smaug recognition element (SRE). Structural studies of the SRE-RNA complex of VTS1p-SAM revealed that the SAM domain primarily recognizes the shape of the RNA fold induced by the Watson-Crick base-pairing in the RNA pentaloop. Only the central G nucleotide is specifically recognized. The VTS1p-SAM domain recognizes SRE-RNAs with a CNGGN pentaloop where N is any nucleotide. The C1-G4 base pair in the wild type can be replaced by any pair of nucleotides that can form base pairs even though the binding affinity is greatest with a pyrimidine in position 1 and a purine in position 4. The interaction thus combines elements of sequence-specific and non-sequence-specific recognitions. The lack of structural rearrangements in either partner following binding is rather intriguing, suggesting that molecular dynamics may play an important role in imparting relaxed specificity with respect to the exact combination of nucleotides in the loop, except for the central nucleotide. In this work, we extend our previous studies of SRE-RNA interaction with VTS1p, by comparing the dynamics of the VTS1p-SAM domain both in its free form and when bound to SRE-RNA. The 1 5 N relaxation studies of backbone dynamics suggest the presence of a dynamic interaction interface, with residues associated with specific G3 recognition becoming more rigid on RNA binding while other regions attain increased flexibility. The results parallel the observations from our studies of dynamics changes in SRE-RNA upon binding to VTS1p-SAM and shows that molecular dynamics could play a crucial role in modulating binding affinity and possibly contribute to the free energy of the interaction through an entropy-driven mechanism. (C) 2009 Elsevier Ltd. All rights reserved.
Keywords: (15)N relaxation; NMR; protein-RNA interaction; SRE-RNA; VTS1p-SAM domain

Investigation of domain structures in monomethoxy poly(ethylene glycol)-b-poly(caprolactone) grafted poly(acrylic acid) by NMR diffusion studies - Tiwari, Neha; Badiger, Manohar Virupax; Rajamohanan, Pattuparambil Ramanpillai; Ravindranathan, Sapna (Polymer International, 2022)
Associating polymers developed by grafting a block copolymer of monomethoxy poly(ethylene glycol)-b-poly(caprolactone) (MPEG-b-PCL) onto poly(acrylic acid) undergo an irreversible sol-gel transition on heating. The influence of various physicochemical parameters on the thermoresponsive behaviour was examined by rheology and NMR studies. Pulsed field gradient NMR diffusion studies were performed to probe the mechanism of thermally induced gelation. Analysis of the diffusion data reveals the presence of loosely and strongly associated structures which respond differently to variation in temperature. It is observed that the polymer solution, which is visibly homogeneous, is heterogeneous on a mesoscopic scale with a distribution of domains. Detailed investigation of the thermally induced sol-gel transition shows that the mechanism of gelation involves irreversible alterations in the domain structure and size. (c) 2022 Society of Industrial Chemistry.
Keywords: associating polymers; hydrophobically modified polymers; NMR diffusion studies; Rheology; sol-gel transition; thermoresponsive polymers

Insights into the structure of sucralfate by advanced solid- and liquid-state NMR - Hareendran, Chaithanya; Ravindranathan, Sapna; Ajithkumar, T. G. (Molecualr Pharmaceutics, 2024)
Sucralfate, which is a sucrose octasulfate aluminum complex, is an active pharmaceutical ingredient (API) falling in the category of cytoprotective agents which are very effective for gastric and duodenal ulcers. On interaction with stomach acid, it ionizes into aluminum and sucrose octasulfate ions to form a protective layer over the ulcerated region inhibiting further attack from acid. The mechanism of action of sucralfate in the context of its structure is not well understood. Considering that at least two forms of this API are available in the market, there are no reports on the various forms of sucralfate and differences in their pharmacological action. We characterized the two forms of sucralfate using multinuclear, multidimensional solid-state NMR, and the results show significant structural differences between them arising from variation in the aluminum environment and the level of hydration. The impact of structural differences on pharmacological action was examined by studying acid-induced Al release by Al-27 liquid-state NMR. The sucralfate, European pharmaceutical standard, Form I, undergoes faster disruption in acid compared to Form II. The difference is explained on the basis of structural differences in the two forms which gives significant insights into the action of sucralfate in relation to its structure.
Keywords: (27)AlMQMAS; H-1-H-1 DQSQ; pharmacological action; solid-stateNMR; sucralfate

Insight Into the Influence of Salinity on Flow and Flocculation Behavior of Acrylamide-Based Cationic Polyelectrolyte - Ranganath, Suresha P.; Kurian, Rachna; Torris, Arun; Khairnar, Ajay; Ravindranathan, Sapna; Rajamohanan, P. R.; Badiger, Manohar V.; Wolf, Bernhard A. (Journal of Applied Polymer Science, 2026)
The viscometric behavior of aqueous solutions of acrylamide and acrylamidopropyl trimethylammonium chloride copolymers (AM-co-APTMAC) with varying cationic content under different salinity conditions was studied. Viscometric measurements were employed to determine intrinsic viscosity and quantify the influence of electrostatic interactions on chain conformation. Rheology experiments were performed to probe dynamic flow behavior under shear to obtain insights into polyelectrolyte viscoelastic properties under conditions mimicking industrial processes. Viscometric and rheology data analysis is augmented with insights from NMR relaxation and pulsed field gradient NMR diffusion experiments. Further, flocculation of kaolin suspensions was studied using aqueous solutions of AM-co-APTMAC copolymers with different charge fractions in the presence and absence of salt. The physicochemical insights on the behavior of AM-co-APTMAC polyelectrolytes in solution from this study could be relevant in practical applications, such as plants that use seawater or in cases where the ionic strength of suspensions is high due to salinity in the medium.
Keywords: copolymers; polyelectrolytes; structure property relationships; theory and modeling